Pleural Effusion in Adults-Etiology, Diagnosis, and Treatment - Jany, Berthold; Welte, Tobias (Deutsches Ärzteblatt international, 2019)
Pleural effusion is common in routine medical practice and can be due to many different underlying diseases. Precise differential diagnostic categorization is essential, as the treatment and prognosis of pleural effusion largely depend on its cause. This review is based on pertinent publications retrieved by a selective search in PubMed and on the authors' personal experience. The most common causes of pleural effusion are congestive heart failure, cancer, pneumonia, and pulmonary embolism. Pleural fluid puncture (pleural tap) enables the differentiation of a transudate from an exudate, which remains, at present, the foundation of the further diagnostic work-up. When a pleural effusion arises in the setting of pneumonia, the potential devel- opment of an empyema must not be overlooked. Lung cancer is the most common cause of malignant pleural effusion, followed by breast cancer. Alongside the treatment of the underlying disease, the specific treatment of pleural effusion ranges from pleurodesis, to thoracoscopy and video-assisted thoracoscopy (with early consultation of a thoracic surgeon), to the placement of a permanently indwelling pleural catheter. The proper treatment of pleural effusion can be determined only after meticulous differential diagnosis. The range of therapeutic options has recently become much wider. More data can be expected in the near future concerning diagnostic test- ing for the etiology of the effusion, better pleurodetic agents, the development of interventional techniques, and the genetic background of the affected patients.